Pengaruh Waktu Dan Katalis Terhadap Pentosa Dan Furfural Pada Hidrolisis Batang Sawit Bebas Pati - Septiani Adeka; Muhammad Iwan Fermi; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Oil palm trunks are agricultural solid waste that has not been used optimally. Oil palm trunks have a high starch content so that they can be used as raw materials for making bioplastics, dextrins and adhesives. The experiment of hydrolisys of starch-free oil palm trunks was intended to study the effect of time and catalyst concentration on the obtained pentoses and furfurals. Hydrolisys of starch-free palm trunks was carried out in batches on a laboratory scale. The experimental variables studied were formic acid concentration 85% by weight, catalyst concentration (0; 0.05; 0.1; 0.15; 0.2% by weight), reaction time (0; 5; 10; 15; 20; 30 . ; 45; 60; 90; 120; 180 minutes) and a solid-to-liquid ratio of 15/1. The experimental results showed that the time and concentration of the catalyst greatly influenced the pentose and furfural in the process of hydrolisys of starch-free oil palm trunks. The levels of pentose and furfural dissolved in the used cooking liquid in this experiment were pentose (0.31-1.37 grams/l) and furfural (1.45-2.95 grams) with the percentage of hemicellulose recovery ranging from (28-57% ).Keywords: palm trunk, starch-free, delignification, organosolv, formic acid